BIBLIOMETRIC ANALYSIS: GOOGLE CLASSROOM ON MATHEMATICS LEARNING IN THE SCOPUS DATABASE USING VOSVIEWER - Siti Adella Wahyuni; Bambang Sri Anggoro; Novian Riskiana Dewi (ZILLZELL MEDIA PRIMA, 2024)
The Covid-19 pandemic has changed the global education paradigm, including in Indonesia which has adopted distance learning to avoid the spread of the virus. In this context, the use of the google classroom digital platform has become very relevant. This study explores the development and publication trends related to the use of google classroom in mathematics learning from 0-2024 years. By utilizing the Scopus database and Publish or Perish software, the analysis showed a significant spike in the number of 121 documents, through the results of screening into 100 articles using the DOI format. 2021 recorded the highest number of citations, with Indonesia as the leading country and Indonesia University of Education as the top institution. University College London recorded the highest number of citations, while the Journal of Physics: Conference Series dominated the publication. Author Dadang Juandi ranked first, while Melissa Bond received the highest citation for an article on